2013
DOI: 10.1161/atvbaha.113.302494
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog-Dependent Regulation of Angiogenesis and Myogenesis Is Impaired in Aged Mice

Abstract: Objective-The purpose of this study is to further document alteration of signal transduction pathways, more particularly of hedgehog (Hh) signaling, causing impaired ischemic muscle repair in old mice. Approach and Results-We used 12-week-old (young mice) and 20-to 24-month-old C57BL/6 mice (old mice) to investigate the activity of Hh signaling in the setting of hindlimb ischemia-induced angiogenesis and skeletal muscle repair. In this model, delayed ischemic muscle repair observed in old mice was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…This finding reveals a new effect of Shh on SMCs, in addition to its previously demonstrated role in proliferation of these cells. [16][17][18] Even if Hh proteins are suggested to act on angiogenesis only indirectly, 12,31,32 ECs were shown to respond to Shh by increasing their migration and the impermeability of the brain endothelium. 33 In the context of growing vessels, SMC-derived Shh may not only act on SMCs themselves, but also on the neighborhood ECs by stimulating their migration and consequently by promoting vessel growth.…”
Section: Discussionmentioning
confidence: 99%
“…This finding reveals a new effect of Shh on SMCs, in addition to its previously demonstrated role in proliferation of these cells. [16][17][18] Even if Hh proteins are suggested to act on angiogenesis only indirectly, 12,31,32 ECs were shown to respond to Shh by increasing their migration and the impermeability of the brain endothelium. 33 In the context of growing vessels, SMC-derived Shh may not only act on SMCs themselves, but also on the neighborhood ECs by stimulating their migration and consequently by promoting vessel growth.…”
Section: Discussionmentioning
confidence: 99%
“…Controversy regarding Shh signaling is also present in vivo since Shh-induced angiogenesis is not affected in Gli1 null-mice (74), whereas capillaries morphogenesis is inhibited by the presence of Gli1 inhibitor GANT61 (70). Impaired angiogenesis in ischemic tissue of middle-aged or old mice is associated with a decrease in Gli1 transcription factor mRNA expression (68, 75). These results reflect the complex interplay between canonical and non-canonical Shh pathways, or at least that of the Gli family of transcription factors, in the regulation of tubulogenesis and angiogenesis processes.…”
Section: Evs Harboring Shh As Vascular and Cardio-protective Deliverymentioning
confidence: 99%
“…Shh can protect neurons against various stresses, including the amyloid β-peptide, high levels of glutamate, hydrogen peroxide, and rotenone, all are molecules or mediators related to ischemic injury or neurodegenerative diseases such as Alzheimer’s disease (AD) and Parkinson’s disease (PD) [53]. It is suggested that Shh may function as an anti-aging signal [33,54] based on several lines of evidence; these include the observations that the total Shh activity or inducibility are notably reduced in older animals [55], the age-related process of cellular senescence is blocked by active Shh signaling [56], and Shh-targeting drugs possess the potential to mitigate aging-related pathological conditions [57]. …”
Section: Introductionmentioning
confidence: 99%